A influência do treinamento de oclusão vascular em relação a dor, hipertrofia e funcionalidade em indivíduos com osteoartrite do joelho - protocolo de revisão sistemática - Dantas, Claudenice Laranjeira (Brasil, 2022)
Recently, studies have shown that the association between low-load exercises and vascular occlusion training has generated muscle hypertrophy in people with Knee Osteoathritis. Therefore, the objective of this study will be to carrv out a systematic review protocol to verify the influence of vascular occlusion training associated with low-intensity exercises in relation to the improvement of pain hypertrophy and functionaly in individuals with Knee Osteoarthritis. The search strategy was carried out in the PeDro, Medline, Central, Embase and Scopus databases, in which the results found will be analyzed and interpreted by the authors, being selected according to the eligibility criteria. Methodological quality and risk of bias will be assessed using the PeDro scale. The selection of articles and data extraction will be done by two reviewers independently. The quantitative data referring to the evaluation of the studies will be presented in tables, and the qualitative data will be described in a narrative way by the authors, from the reading of the articles. The results of this review will serve to better understand the application of vascular occlusion training during physical therapy rehabilitation in patients with Knee Osteoarthritis and if really influences the improvement of pain, hypertrophy and functionality of these individuals.